2022
DOI: 10.1128/aem.00952-22
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolome Analysis Revealing the Improved ε-Poly- l -Lysine Production Induced by a Microbial Call from Botrytis cinerea

Abstract: This work identified the role of microbial elicitors on ε-PL production and disclosed the underlying mechanism through analysis of gene transcription, key enzyme activities, and intracellular metabolite pools, including transcriptome and metabolome analysis. It was the first report for the inducing effects of the “microbial call” to Streptomyces albulus and ε-PL biosynthesis, and these elicitors could be potentially obtained from decayed fruits infected by Botrytis cinerea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…As a biocontrol agent secreted by S. albulus, ε-PL exhibited high inhibitory efficiency on the mycelial elongation of B. cinerea (Figure 1A and Table 1). Inspired by natural microbial interactions and competition, we proposed an innovative strategy to enhance ε-PL production by incorporating biomass extracts from B. cinerea, resulting in a 34% increase in ε-PL production [27]. However, it remained unclear whether the impact of microbial stress on ε-PL biosynthesis was direct or indirect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a biocontrol agent secreted by S. albulus, ε-PL exhibited high inhibitory efficiency on the mycelial elongation of B. cinerea (Figure 1A and Table 1). Inspired by natural microbial interactions and competition, we proposed an innovative strategy to enhance ε-PL production by incorporating biomass extracts from B. cinerea, resulting in a 34% increase in ε-PL production [27]. However, it remained unclear whether the impact of microbial stress on ε-PL biosynthesis was direct or indirect.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing inspiration from microbial interactions and competition, we hypothesized that ε-PL production would not be upregulated until an aggression signal is received from other microorganisms, suggesting that microbial signaling may play a crucial role in the biosynthesis of ε-PL. Our previous study demonstrated the positive impact of biomass extracts from B. cinerea on ε-PL biosynthesis [27]. However, it remains unclear whether the influence of B. cinerea signaling on ε-PL biosynthesis is direct or indirect.…”
Section: Introductionmentioning
confidence: 97%